Soil erosion in South Africa - Kitto, P H (Rhodes University College, Faculty of Science, Department of Chemistry, 1936)
The development of Soil Science in western Europe, eastern North America, and later in other countries, which, in its modern form only started about the beginning of the last century, might be said to mark the first step in the consideration of Soil Erosion from a scientific aspect, although it was some time before scientists began to concentrate on and study the problem as one which demanded a detailed investigation. Empirically, erosion has been noted and, where the value of the land warranted it, practical methods adopted for its control, in many cases with no small measure of success, for centuries, but the methods adopted were localised to small regions, and the major destruction went on unchecked. The seriousness of this destruction was usually not realised until too late, and striking examples exist of the complete desiccation resulting from this neglect. Those of China, Arabia, Mesopotamia and other countries have often been quoted, and need not be described again here.
Keywords: Soil erosion -- South Africa; Soils Analysis; Wind erosion; Water erosion